Neural Lineage Differentiation From Pluripotent Stem Cells to Mimic Human Brain Tissues - Hong, Yean Ju; Do, Jeong Tae (Frontiers in Bioengineering and Biotechnology, 2019)
Recent advances in induced pluripotent stem cell (iPSC) research have turned limitations of prior and current research into possibilities. iPSCs can differentiate into the desired cell types, are easier to obtain than embryonic stem cells (ESCs), and more importantly, in case they are to be used in research on diseases, they can be obtained directly from the patient. With these advantages, differentiation of iPSCs into various cell types has been conducted in the fields of basic development, cell physiology, and cell therapy research. Differentiation of stem cells into nervous cells has been prevalent among all cell types studied. Starting with the monolayer 2D differentiation method where cells were attached to a dish, substantial efforts have been made to better mimic the in vivo environment and produce cells grown in vitro that closely resemble in vivo state cells. Having surpassed the stage of 3D differentiation, we have now reached the stage of creating tissues called organoids that resemble organs, rather than growing simple cells. In this review, we focus on the central nervous system (CNS) and describe the challenges faced in 2D and 3D differentiation research studies and the processes of overcoming them. We also discuss current studies and future perspectives on brain organoid researches.